ANALISIS PT. NESTLÉ INDONESIA DALAM MENGELOLA PERUBAHAN DAN MENANGGAPI PERSAINGAN DI ERA SOCIETY 5.0 BERDASARKAN MODEL KNOSTER - Firgie, Daffaessa; Haludin, Guntur; Putri, Dhiza; Septiyani, Ais; Putra, Bima Aji; Chaska, M. Hilmana (Bussman Journal : Indonesian Journal of Business and Management, 2024)
The Society 5.0 era brings major challenges for global companies, especially in terms of rapid and complex changes triggered by technologies such as artificial intelligence, the Internet of Things, and big data. PT. Nestlé Indonesia, as one of the major companies in the food and beverage industry, must manage change effectively to remain relevant and competitive in the global market. This study aims to analyze how PT. Nestlé Indonesia manages change and faces competition in the digital era using the Knoster Model as an analytical framework. The research method used is a qualitative approach with secondary data analysis from various sources, such as annual reports, articles, and company documents. The results of the study indicate that the success of change at PT. Nestlé Indonesia depends on clear vision communication, employee skill development, and motivation and support provided by leaders. The Knoster Model provides useful insights for planning and managing change by considering various important elements, such as skills, incentives, and leadership. This study also provides practical recommendations for Nestlé Indonesia in facing the challenges of change in the future.